2019
DOI: 10.1111/cod.13417
|View full text |Cite
|
Sign up to set email alerts
|

Contact allergy to formaldehyde releasers. Prospective multicenter study

Abstract: The prevalence of sensitization to formaldehyde releasers (FRs) differs according to geographic area and has changed over time. Several factors may influence prevalence, including different patch test systems or concentrations or the allergen selection in different baseline patch test series, habits of the populations, and regulations and legal concentration limits in cosmetics. 1,2 Quaterium-15 had been SANZ-SÁNCHEZ ET AL. 173

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 9 publications
1
12
1
Order By: Relevance
“…21,35,36 Although its counterpart imidazolidinyl urea is more widely used, diazolidinyl urea is a more-potent sensitizer, accounting for higher overall rates of sensitization, being more pronounced in the United States (2%-4%) as compared to Europe (0.5%-1.5%). 13,23,[35][36] Because diazolidinyl urea is less frequently used in occupational products, data on its importance as an occupational allergen are lacking.…”
Section: Prevalence Of Sensitizationmentioning
confidence: 99%
See 2 more Smart Citations
“…21,35,36 Although its counterpart imidazolidinyl urea is more widely used, diazolidinyl urea is a more-potent sensitizer, accounting for higher overall rates of sensitization, being more pronounced in the United States (2%-4%) as compared to Europe (0.5%-1.5%). 13,23,[35][36] Because diazolidinyl urea is less frequently used in occupational products, data on its importance as an occupational allergen are lacking.…”
Section: Prevalence Of Sensitizationmentioning
confidence: 99%
“…to be sensitized to this FR, albeit showing a decreasing trend, whereas in Europe the sensitization rate is only 0.5%. 13,23,35 4 | CLINICAL PICTURE…”
Section: Prevalence Of Sensitizationmentioning
confidence: 99%
See 1 more Smart Citation
“…There are also a number of formaldehyde-releasing preservatives, including DMDM hydantoin, quarternium-15, imidazolidinyl urea, diazolidinyl urea, and 2-bromo-2nitropropane-1,3-diol, with only the latter 4 included in the standard thin-layer rapid use epicutaneous patch test series. 40 Formaldehyde-releasing preservatives release formaldehyde in the presence of water. 41 Formaldehyde itself can be patch tested at a 1% or 2% concentration, though the 2% concentration may yield more positive results.…”
Section: Formaldehydementioning
confidence: 99%
“…Data from a multicenter prospective study in Spain, which included 18 hospitals, showed that from 4088 patch tested patients, 70 tested positive for formaldehyde releasers (1.7%). This incidence was judged as being low despite the wide-spread use of formaldehyde-releasing chemicals in Spain ( Sanz-Sanchez et al, 2020 ) [MC]. A case of occupational allergic contact dermatitis caused by formaldehyde and 2-bromo-2-nitropropane-1,3-diol (bronopol) contained in a polypropylene surgical mask was described.…”
Section: Aldehydes [Sed-15 1439 1513; Seda-31 409; Seda-32 437; Seda-33 479; Seda-34 377; Seda-36 339; Seda-37 273; Seda-38 211mentioning
confidence: 99%